PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KETERAMPILAN BERPIKIR SPASIAL SISWA SMA - Giofani Ginolla Ardiyanto; Sri Astutik; Era Iswara Pangastuti (Universitas Negeri Padang, 2023)
The purpose of this study was to examine the Contextual Teaching and Learning (CTL) learning model for high school spatial thinking skills. This type of research is quasi-experimental with the experimental class and the control class as the research sample. The CTL model has 7 model syntaxes namely constructivism, inquiry, learning community, modeling, reflection and authentic assessment. The material taught in this learning model is atmospheric material in class X. Before conducting the research, the researcher first conducted normality tests and homogeneity tests to determine the experimental class and control class in the study population. The results showed that the average value of students in the experimental class was 85.25, while in the control class it was 71.6286. After that, a t-test was carried out in both classes to determine the effect of the given model. The results of the t-test test carried out produced the result that the Contextual Teaching and Learning (CTL) model had an effect on spatial thinking skills with a significance result of the t-test test of 0.000. The indicator that gets the highest score is the hierarchical indicator, which is getting 100%.